2020
DOI: 10.3390/ijerph17218199
|View full text |Cite
|
Sign up to set email alerts
|

Global Prevalence of Macroprolactinemia among Patients with Hyperprolactinemia: A Systematic Review and Meta-Analysis

Abstract: Hyperprolactinemia (hPRL) often poses a diagnostic dilemma due to the presence of macroprolactin. Understanding the prevalence of macroprolactinemia (mPRL) has an important implication in managing patients with hPRL. The primary aim of this study was to determine the prevalence of mPRL globally and to explore selected factors influencing the prevalence estimate. Studies with original data related to the prevalence of mPRL among patients with hPRL from inception to March 2020 were identified, and a random effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 79 publications
1
13
0
1
Order By: Relevance
“…The overall global prevalence estimate of macroprolactin is 18.9% (95% CI: 15.8%, 22.1%) which necessitates screening for before investigating for causes of elevated prolactin. 10 …”
Section: Discussionmentioning
confidence: 99%
“…The overall global prevalence estimate of macroprolactin is 18.9% (95% CI: 15.8%, 22.1%) which necessitates screening for before investigating for causes of elevated prolactin. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, Soh and colleagues recently pooled data from 67 studies (n = 3770) and reported an overall prevalence of 18.9% for macroprolactinemia in patients with hyperprolactinemia [12]). However, the prevalence reported in this study is lower compared with the prevalence reported in other settings.…”
Section: Discussionmentioning
confidence: 73%
“…The prevalence of MP in our study was 8.3%. In a meta-analysis of 67 studies, the overall prevalence of MP was 19% but varied from 0 to 56% among the different studies [9]. This wide variability could largely be attributed to the difference in prolactin assays used in these studies.…”
Section: Discussionmentioning
confidence: 99%